Media and Confidence in the Police: Differences across Race/Ethnicity - Rosenberger, Jared S. (American journal of criminal justice, 2022)
A substantial body of literature connects direct experience with crime and the criminal justice system to public confidence in the police (Bradford Policing and Society, 24(1): 22-43, 2014; Gibson et al. American Journal of Political Science 47: 354-367, 2003, Political Research Quarterly, 58: 187-201, 2005; Sargeant Policing and Society 27: 927-940, 2017). However, most citizens have limited direct interaction with the police (Roberts & Doob Law and Human Behavior 14: 451-468 , 1990; Surette, 2007), justifying research exploring the impact of media consumption on attitudes toward the police. This study examines the impact of news consumption through television, the internet, and social media on confidence in the police across race/ethnicity. The study utilizes a national non-full probability sample of 500 White, Black, and Hispanic/Latinx respondents. Findings suggest that race/ethnicity mediates the relationship between news source and attitudes toward the police. Implications are discussed.